ChemInform Abstract: One‐Step Metal‐Free Construction of Fluorescent 5‐Aryl‐2, 3‐dicyanofurans from Simple Aryl Ketones with DDQ. Issue 29 (22nd July 2014) - Li, Jiang‐Sheng; Cai, Fei‐Fei; Li, Zhi‐Wei; Liu, Wei‐Dong; Simpson, Jim; Xue, Yuan; Pang, Huai‐Lin; Huang, Peng‐Mian; Cao, Zhong; Li, Dao‐Lin
Abstract Title compounds [(III), (V), and (VII)] are synthesized by treatment of electron‐rich aryl ketones with DDQ.